Assessment of Accuracy of Continuous Noninvasive versus Invasive Method of Hemoglobin Estimation in Patients Undergoing Pituitary Surgery - Kapoor, Indu; Mahajan, Charu; Mamuliya, Ruhi; Prabhakar, Hemanshu (Journal of Neuroanaesthesiology and Critical Care, 2018)
Aim Determination of hemoglobin (Hb) concentration by standard methods is time consuming, invasive, and intermittent. Noninvasive (NI) methods of Hb estimation are less time consuming, and reduce the risk of infection, number of required working personnel, and long-term costs. In this study, we aimed to find the accuracy of Hb values at various time points using noninvasive (NI) Hb monitoring and standard invasive techniques such as laboratory (LabHb) and arterial blood gas (ABG).Methods All American Society of Anesthesiologists (ASA) physical grade I and II adult patients between 18 and 65 years of either gender undergoing pituitary surgery under general anesthesia were included over a period of 1 year. Samples were collected for Hb estimation from the arterial line (aHb) using ABG analyzer machine and LabHb using automated Hb analyzer. Simultaneously, Hb reading from the NI Hb monitor was recorded using Masimo Spot Hemoglobin Check Device. Bland–Altman plot was used to find out agreement between Hb values drawn from three different techniques. A p-value < 0.05 was considered significant.Results A total of 30 patients participated in the study. The male to female ratio was 13:17. Statistical analysis showed poor correlation between the invasive and NI methods of Hb estimation.Conclusion NI method of Hb estimation may be successfully used in clinical practice, replacing estimation from ABG analysis or laboratory tests. However, NI method cannot replace the invasive methods of Hb estimation.
Keywords: noninvasive hemoglobin monitor; invasive hemoglobin monitor; blood loss; arterial blood gas; laboratory test